"Learn the vosotros [you conjugation] to speak with Spaniards in their language": Linguistic identification in Argentina as a tension between pride and underestimation - López García, María (Historia y Memoria de la Educación, 2015)
This paper analyses the construction of a linguistic identity in Argentina through school textbooks. The basic assumption is that the Argentinean school continues to exhibit the 19th century imaginary of being the agency for the diffusion of knowledge and the construction of citizenship, but that today, the instruments that it employs for teaching and the laws that govern the functioning of these materials are strongly influenced by the rules of the market economy. Therefore, the Spanish language, bearer of the Hispanic heritage and a binding element of the Argentinean school of the 19th century, is no longer subject to territorial limits (and thus, to the particularities of linguistic variety) because, by moving beyond these limits, language is able to more easily adapt itself to the expansionist tendencies of the market. In the framework of linguistics politics and relying on the theories that study the role of emotions in the process of self-identification, the article analyses the coexistence of «globalized» language and dialect identification. The tension between these two aspects of language generates identifications of contrasting natures among citizens/speakers; on the one hand, linguistic practice in school is associated with belonging to the nation, while at the same time the use of global textbooks and manuals tends to inhibit the use of language featuring particular local or national elements. The analysis of regional linguistic features in a sample of textbooks (from the present and from past milestones in Argentina) evidences overlapping identities discursively generated between a de-territorialized language and a curricular pattern that promotes the appreciation of varieties.